The Research of Long-Optical-Path Visible Laser Polarization Characteristics in Smoke Environment - Juntong, Zhan; Shicheng, Bao; Su, Zhang; Qiang, Fu; Yingchao, Li; Jin, Duan; Wei, Zhang (Frontiers in Physics, 2022)
The concentration of smoke environment can cause obvious interference to visible light in-tensity imaging, and it is a non-negligible factor in the polarized imaging of ground-based targets. Smoke particles cause severe scattering of photon intensity, resulting in polarization. In this case, low visibility targets can be effectively identified by detecting the polarization dimension of targets. However, the polarization transmission of smoke environment is unclear, and the theoretical simulation lacks experimental reliability verification. Aiming at this problem, this study constructs a polarization transmission model in a smoke environment and simulates and analyzes the scattering of visible polarized light at 450, 532, and 671 nm under different smoke densities. The optical thickness is determined to establish a reliable connection between the simulation and the external field long optical path test and verify the transmission of polarized light. Results show that the method has a 60% confidence in the polarization transmission model. With the increase in optical thickness, the degree of polarization (DOP) of the three wavelengths in the visible light band decreases, and the DOP of each polarized light decreases. No obvious difference is found between the DOPs of circularly polarized light at 450 nm and linearly polarized light. The DOP of circularly polarized light at 532 nm is 1%–5% higher than that of linearly polarized light, 1%–10% higher than that of outdoor test, 1%–5% higher than that of circularly polarized light at 671 nm, and 2%–15% higher than that of outdoor test. Therefore, the shorter the wavelength in the visible band, the higher the DOP. With the increase in wavelength, the polarization characteristics of circularly polarized light are gradually better than those of linearly polarized light.